Determination analysis of realization in foreign investment: A case in West Java - Assyifa Zahra Namira (Sebelas Maret Business Review, 2024)
In 2024, West Java Province aims to boost foreign investment to 250 trillion rupiah, maintaining its leading position in investment realization. This research examines factors influencing foreign investment in West Java, including SMEs (Usaha Mikro, Kecil, dan Menengah-UMKM), expenditure per capita, flood, waste, productive land, and unemployment. Prior strategies focused on direct engagement with foreign investors but neglected other critical determinants. This study investigates key sectors and economic indicators to provide a comprehensive analysis. The data used in this paper is a balanced panel of 27 residences and cities in West Java with an annual period from 2018 to 2022. We choose REM as the best model using panel data tests, including Chow, Hausman, and BPLM. This paper found that SMES, expenditure, productive land, and unemployment significantly positively affect the predictor. On the other hand, how floods and waste are handled has an insignificant effect on the predictor.